"Inside Disc Out" Discectomy for the Treatment of Discogenic Lumbar Spinal Canal Stenosis under the Intervertebral Foramen Endoscope. Issue 1 (18th November 2022) - Sun, Shunqiang; Wang, Lu; Xue, Yuan
Abstract : Objective: Conventional posterior‐approach decompression surgeries have a higher risk of nerve root injury and dura laceration. We explore the therapeutic strategy and effect of "inside disc out" discectomy under intervertebral foramen endoscope technique for discogenic lumbar spinal canal stenosis (DLSS) treatment. Methods: Twenty‐nine patients with DLSS in the responsible segment were treated with "inside disc out" discectomy under intervertebral foramen endoscope technique between October 2017 to October 2019. Lower limb and back pain were recorded before operation, and visual analogue scale (VAS) score and Oswestry disability index (ODI) were recorded for lower limb and back pain at 1, 3, 6, and 12 months postoperatively. The postoperative effects were evaluated using the modified MacNab method for all the patients. Results: All 29 patients successfully completed the operation. The operation time was 75–120 min, with an average of 90 ± 17 min. Postoperative lumbar CT examinations of all the patients showed full decompression of the spinal cord with no residual pressure. The average follow‐up time for all the patients was 13 ± 3.5 months (12–18 months). The VAS score for lower back and lower limb pain was 7.52 ± 1.25 before the operation, and 1.80 ± 0.63, 1.33 ± 0.88, 1.07 ± 0.89, and 0.81 ± 0.51 at 1, 3, 6, and 12 months after the surgery, respectively. The Oswestry dysfunction index was 59.43 ± 10.04 before surgery and 29.67 ± 10.35, 21.13 ± 9.32, 14.52 ± 5.98, and 9.84 ± 4.68 at 1, 3, 6, and 12 months after the surgery, respectively. The VAS score and ODI index of low back and lower limb pain at different time points after the surgery were significantly improved compared to those before the surgery ( P < 0.01). The effect of the modified MacNab was excellent in 26 patients, good in two patients, and fair in one patient. The excellent and good rates were 91.4%. Among them, one patient had symptoms of hyperesthesia in the anterior aspect of the thigh and decreased quadriceps muscle strength after lumbar 4/5 segment endoscopic surgery. After symptomatic and conservative treatment, the symptoms disappeared 4 weeks postoperatively, and there were no other serious surgical complications. Conclusions: Following the "inside disc out" discectomy under intervertebral foramen endoscope protocols, the risk of nerve injury can greatly be reduced, with good postoperative efficacy. Overall, the procedure is safe and feasible for DLSS treatment. Abstract : The therapeutic strategy and effect of "inside disc out" discectomy under intervertebral foramen endoscope technique for discogenic lumbar spinal canal stenosis (DLSS) treatment is relatively safe and effective.